2000
DOI: 10.1095/biolreprod63.5.1383
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in Rat Testicular Interstitial Oxygen Tensions Are Linked to Testicular Vasomotion: Persistence after Repair of Torsion1

Abstract: Testicular microvascular blood flow is known to exhibit vasomotion, which has been shown to be significantly altered in the short term following the repair of testicular torsion. This loss of vasomotion may ultimately be responsible for the loss of spermatogenesis observed after testicular torsion in rats. In the present study, testicular vasomotion and interstitial oxygen tensions were simultaneously measured prior to, during, and at various time points after repair of testicular torsion in the rat. Testicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 25 publications
4
53
0
Order By: Relevance
“…An in vivo model is preferred to understand testicular physiology, as there are autoprotective mechanisms against low O 2 tension in the testis (Elshaari et al 2012) and natural antioxidant systems (Aitken and Roman 2008;Reyes et al 2012) that are difficult or impossible to replicate in an in vitro model. Furthermore, under heat stress, testicular vasomotion (rhythmic tone variation in blood vessels) is greatly suppressed (Setchell et al 1995) which can impair testicular function (Lysiak et al 2000;Aalkjaer et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…An in vivo model is preferred to understand testicular physiology, as there are autoprotective mechanisms against low O 2 tension in the testis (Elshaari et al 2012) and natural antioxidant systems (Aitken and Roman 2008;Reyes et al 2012) that are difficult or impossible to replicate in an in vitro model. Furthermore, under heat stress, testicular vasomotion (rhythmic tone variation in blood vessels) is greatly suppressed (Setchell et al 1995) which can impair testicular function (Lysiak et al 2000;Aalkjaer et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…However, blood vessels are located exclusively between the tubules, and oxygen reaches the lumen of the seminiferous tubules only by diffusion. The seminiferous epithelium was speculated to operate on the verge of hypoxia because the testicular PO 2 is relatively low, oxygen extraction is highly related to the metabolic demands of spermatogenesis, oxygen diffusion distance is comparatively long, and the testis has little capacity to increase total blood flow (Lysiak et al 2000). Furthermore, exposure to hypoxia results in distribution of blood flow to the vital organs including brain and heart, and decrease in testicular blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…However, blood vessels are located exclusively between the tubules, and oxygen reaches the lumen of the seminiferous tubules only by diffusion. The seminiferous epithelium was speculated to operate on the verge of hypoxia because the testicular partial pressure of oxygen (PO 2 ) is relatively low, oxygen extraction is highly related to the metabolic demands of spermatogenesis, oxygen diffusion distance is comparatively long, and the testis has little capacity to increase total blood flow (Lysiak et al 2000). Furthermore, exposure to hypoxia results in redistribution of blood flow to the vital organs including brain and heart and decrease in testicular blood flow, Koskinen et al (2000) reported that breathing 10 % O 2 / 90 % N 2 resulted in a 24 % decrease in testicular blood flow, but a 23 % increase in ce- rebral blood flow.…”
Section: Discussionmentioning
confidence: 99%